Analysis of CBSE Question Papers in Biology - Farkya, Sunita; Tripathi, B.K. (SCHOOL SCIENCE, 2014)
Quantitative and qualitative analysis of CBSE question papers in the subject Biology was done for the years 2012, 2013 and 2014. Questions asked in the question papers under the study were analysed on several parameters, including mental processes, form of question, difficulty level, content, marking scheme, time allotted for reflection, etc. A changing trend has been observed in the questions in the question papers from the years 2012 to 2014 that the assessment of rote memorisation has been replaced by the assessment of higher order thinking skills. It was observed that in the year 2013, value-based questions were introduced with a weightage of 7 per cent, which got reduced to 4 per cent of the total marks in the year 2014